On the problem of forming of culture of religious tolerance in Kazakhstan - Ismagambetova, Zuchra (Chabaršy. Dintanu serijasy, 2017)
For the Kazakh society, one of the topical problems is the formation of culture of religious tolerance. In this article, the authors set out to determine the main problems of the formation of culture of religious tolerance in the Kazakh society. The authors show the necessity of forming tolerance in the Kazakh society. The necessity of forming the principle of tolerance in inter-ethnic and inter-religious relations is pointed out.The authors show the complexity and importance of the formation of religious tolerance in inter-ethnic and inter-confessional relations. The authors note the influence of globalization and modernization on interfaith and interethnic relations. The authors note some of the threats that exist in the society.In the article the authors cite the results of sociological study of the problem of tolerance among students, a number of problem areas are shown that are necessary for understanding the necessity of solving this problem.